Some microstructural properties of zinc borosilicate glass as a possible matrix in the immobilization of various wastes - Musić, Svetozar (Array, 2019)
Zinc borosilicate glass with optimized chemical composition was synthesized and doped with 5 wt % α-Fe2O3. XRD, 57Fe Mössbauer, FT-IR, UV/Vis/NIR and FE SEM were used as the characterization methods. XRD showed the amorphous nature of the samples synthesized. 57Fe Mössbauer spectra confirmed the superposition of Fe3+ in tetrahedral and Fe2+ in octahedral positions. FT-IR spectra showed general features characteristic of different borosilicate glasses. The NIR band at 1116 nm in the UV/Vis/NIR spectrum was assigned to the Fe2+ transition, whereas the Fe3+ transition bands could not be assigned due to the overlapping of several spectral bands of different origin in the UV region centered at 282 nm and the Vis region between 415 to 496 nm. Zinc borosilicate glass as synthesized can be considered as a possible matrix in the immobilization of nonradioactive as well as radioactive wastes.